Efficient injection of an intense positron beam into a dipole magnetic field - H Saitoh; J Stanja; E V Stenson; U Hergenhahn; H Niemann; T Sunn Pedersen; M R Stoneking; C Piochacz; C Hugenschmidt (New Journal of Physics, 2015)
We have demonstrated efficient injection and trapping of a cold positron beam in a dipole magnetic field configuration. The intense 5 eV positron beam was provided by the NEutron induced POsitron source MUniCh facility at the Heinz Maier-Leibnitz Zentrum, and transported into the confinement region of the dipole field trap generated by a supported, permanent magnet with 0.6 T strength at the pole faces. We achieved transport into the region of field lines that do not intersect the outer wall using the ${\bf{E}}× {\bf{B}}$ drift of the positron beam between a pair of tailored plates that created the electric field. We present evidence that up to 38% of the beam particles are able to reach the intended confinement region and make at least a 180° rotation around the magnet where they annihilate on an insertable target. When the target is removed and the ${\bf{E}}× {\bf{B}}$ plate voltages are switched off, confinement of a small population persists for on the order of 1 ms. These results lend optimism to our larger aims to apply a magnetic dipole field configuration for trapping of both positrons and electrons in order to test predictions of the unique properties of a pair plasma.